"What's fair to an individual is not always fair to a population": A qualitative study of patients and their health professionals using the Cancer Drugs Fund. Issue 8 (August 2019) - Chamberlain, Charlotte; Owen-Smith, Amanda; MacKichan, Fiona; Donovan, Jenny L.; Hollingworth, William
Highlights: Exploring resource allocation perspectives of patients with incurable cancer and their professionals using the CDF is novel. Most patients and health professionals emphasised prioritising quality over quantity at the end of life. A minority of patients and professionals felt time at the end of life had added value over other times of life. While patients and oncologists appreciated the drugs available through the CDF, most expressed concern about its fairness. Abstract: Objective: To understand the values attached to cancer treatment at the end of life (EoL) to inform policy decisions around the Cancer Drugs Fund (CDF) and the National Institute for Health and Care Excellence (NICE) EoL criterion. Design: Semi-structured interviews with patients and health professionals. Purposive recruitment was performed iteratively alongside analysis of interview transcripts using constant comparison. Participants: Patients with incurable prostate and colorectal cancer (n = 22) who received drugs funded through the CDF and oncologists and palliative care professionals (n = 16) treating patients on CDF drugs. Results: While the majority of patient and oncologist participants expressed gratitude for access to the CDF, some patient participants reported experiencing a sense of guilt, and many oncologists admitted to concern about the justice of a ring-fenced fund solely for anti-cancer drugs. For patient and professional participants, cancer drugs were not necessarily seen as a funding priority over other calls on the NHS purse. Overall, patients and health professionals emphasised prioritising quality over quantity at the end of life, with only a minority describing improved quality of life at the end of life which added value. Conclusion: While patients and oncologists appreciated the drugs available through the CDF, most expressed concern about its fairness. Competing participant views about the added value of the end of life is challenging for resource allocation.